Hepatic Metastasis Revealing a Melanoma of the Penis: Case Report - Meriem Boui; Nabil Hammoune; Badr Slioui; Zakaria Zouaki; Mehdi Atmane; Abdelilah Mouhsine; Mohamed Amine Haouane; Mohamed Amine Azami; Mohamed Kaakoua; Ismail Assadi; Mohammed Boui; Ahmed Bouhamidi (JMIR Publications, 2022)
Melanoma of the penis is a rare tumor with a poor prognosis. We report the case of a 73-year-old patient with no significant medical history, admitted for deterioration of the general condition and bilateral inguinal lymph nodes. An abdominal ultrasound and thoraco-abdomino-pelvic CT (computed tomography) scan revealed metastatic liver nodules, the tumoral nature of which was confirmed by an anatomopathological examination. Further clinical examination revealed papular and ulcerated lesions of the penis located at the urethral meatus and glans penis. These lesions were biopsied and histologically assessed as melanoma. The contribution of imaging in penile tumors is generally not useful for diagnosis as clinical examination is key. However, it has its place in the assessment of locoregional and distant extension. In our case, it was the distant lesions that helped orient the diagnosis. The patient underwent immunotherapical treatment and is still alive 19 months after the diagnosis.